The influence of CSR disclosure on financial performance: the moderating role of independent commissioners - Aminatuzzuhro,; Setiawan, Doddy; Widagdo, Ari K. (Frontiers in Sustainability, 2025)
Financial performance analysis can help companies understand their financial strengths and weaknesses, and make strategic decisions to improve profitability and sustainability. Corporate Social Responsibility (CSR) has become an important aspect of business strategy for companies, including state-owned enterprises, to improve their reputation and sustainability. State-owned enterprises (SOEs) are business entities whose capital is wholly or largely owned by the state, with the aim of managing strategic business activities and providing benefits to the community and the state. SOEs can take the form of limited liability companies, public companies, or other institutions. Research on the impact of CSR on the financial performance of SOEs shows that CSR can have a positive impact on financial performance by increasing stakeholder trust, reducing risk, and improving operational efficiency. Here, we demonstrate that independent directors can strengthen the influence of CSR disclosure on financial performance, thereby providing important insights for management and shareholders regarding the importance of involvement in CSR disclosure and the presence of independent directors to improve a company’s financial performance. Compared to previous studies that may have focused solely on the impact of CSR on financial performance, the results of this study show that the presence of independent commissioners can strengthen the positive relationship between CSR disclosure and a company’s financial performance. Independent commissioners ensure that companies comply with applicable regulations and business ethics, and improve corporate transparency and accountability. The results of this study also show that effective CSR strategies must be supported by good corporate governance structures.